2018
DOI: 10.1016/j.biocon.2018.04.040
|View full text |Cite
|
Sign up to set email alerts
|

Accounting for habitat structural complexity improves the assessment of performance in no-take marine reserves

Abstract: Seascape variability may confound assessments on the effectiveness of no-take marine reserves (NTMRs) in conserving biodiversity. In most cases baseline data are lacking, resulting in evaluations of NTMR effectiveness being Control Impact (CI) assessments. Even with independent replicate areas among management zones, this approach can make it difficult to detect zone effects if seascape attributes, such as habitat structural complexity varies among experimental areas. To determine the importance of structural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 46 publications
2
34
0
Order By: Relevance
“…For example, rates of redistribution in the poleward edge of core environmental habitat for species with the strongest associations with topographic habitat (bonito and kingfish) were reduced by 60.4 and 58.3 km per decade, respectively, while a reduction of 7.1 km per decade was identified for dolphinfish, which had a weak association with seascape topography. These findings are supported by the positive effect of topographic features on the relative abundance of bonito and kingfish found by Hobday and Campbell (2009) and Rees et al (2018), and suggest that pelagic fishes that do not exhibit these habitat preferences may be undergoing more rapid range shifts than fishes that actively associate with topographic features. Thus, the effect of topographic habitat on pelagic fish distributions may be an important driver of variation in rates of climatedriven range shifts, which may manifest in punctuated rather than gradual shifts in species distributions depending on the presence or absence of topographic features throughout the seascape.…”
Section: Discussionmentioning
confidence: 55%
“…For example, rates of redistribution in the poleward edge of core environmental habitat for species with the strongest associations with topographic habitat (bonito and kingfish) were reduced by 60.4 and 58.3 km per decade, respectively, while a reduction of 7.1 km per decade was identified for dolphinfish, which had a weak association with seascape topography. These findings are supported by the positive effect of topographic features on the relative abundance of bonito and kingfish found by Hobday and Campbell (2009) and Rees et al (2018), and suggest that pelagic fishes that do not exhibit these habitat preferences may be undergoing more rapid range shifts than fishes that actively associate with topographic features. Thus, the effect of topographic habitat on pelagic fish distributions may be an important driver of variation in rates of climatedriven range shifts, which may manifest in punctuated rather than gradual shifts in species distributions depending on the presence or absence of topographic features throughout the seascape.…”
Section: Discussionmentioning
confidence: 55%
“…These mostly include Rugosity , VerRelief, depth heterogeneity indices , FractalDim , different substrate hole properties (amount, size, density etc.) and visual estimation (Almany, 2004; Ferreira et al., 2001; Nash et al., 2013; Rees et al., 2018; Walker et al., 2009; Wilson et al., 2007). We found that more than half of the studies reviewed incorporated only one index to quantify complexity, and that the use of several indices remains relatively low (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…The swath acoustic data were beneficial in selecting reefs to sample, but they can also be used to derive metrics that can possibly predict the spatial distribution of species richness, species of interest and all fishery target species pooled together. The derivation of habitat metrics from swath acoustic data can provide various levels of explanatory or predictive ability relating to fish assemblage composition and distribution [ 27 , 31 , 34 , 78 , 79 ]. In this study, rugosity, slope or relief were selected in the ‘best’ models explaining the variability in many aspects of the fish assemblages that were sampled.…”
Section: Discussionmentioning
confidence: 99%
“…Temperate mesophotic reefs have important biodiversity, social and economic values [ 16 , 25 ], so understanding the characteristics of their associated fish assemblages is fundamental to effectively managing them. Habitat type (coral, sponge, bare) and complexity (relief, rugosity, curvature) are known to be important in structuring fish assemblages [ 26 31 ]. Habitat complexity is considered as the variance in surface structure of the reef and can be defined in terms of relief, slope, rugosity, surface area, and other factors [ 28 , 32 ].…”
Section: Introductionmentioning
confidence: 99%